Two Generalizations of a Deposit–Refund System - Fullerton, Don; Wolverton, Ann (American Economic Review, 2000)
This paper suggests two generalizations of the deposit-refund idea. In the first, we apply the idea not just to solid waste materials, but to any waste from production or consumption including wastes that may be solid, gaseous, or liquid. Using a simple general equilibrium model, we derive the optimal combination of a tax on a purchased commodity and subsidy to a clean' activity (such as emission abatement, recycling, or disposal in a sanitary landfill). This two-part instrument' is equivalent to a Pigovian tax on the dirty' activity (such as emissions, dumping, or litter). In the second generalization, we consider the case where government must use distorting taxes on labor and capital incomes. To help meet the revenue requirement, would the optimal deposit be raised and the refund reduced? We derive the second-best revenue-raising DRS or two-part instrument to answer that question.